Investigating molecular determinants of FIV pathogenesis - Thompson, Jesse Alan, author; VandeWoude, Susan, advisor (Colorado State University. Libraries, 2009)
Five FIV clades have been identified and are distinguished by envelope sequence. Two isolates, FIV-PPR and FIV-CPG (molecular clone FIV-C36), belonging to clades A and C, respectively, are variable with regard to disease potential. Chimeric viruses constructed between phenotypically distinct strains of FIV are potentially useful tools to identify molecular determinants of virulence. Several chimeric constructs were therefore developed by exchanging elements between FIV-C36 and FIV-PPR. FIV-PCenv and FIV-PC3'LTR were two resulting chimeras that were capable of competent in vitro replication. Studies in Chapter One aimed to characterize these viruses in the domestic cat model and to test the hypothesis that elements surrounding the env region contribute to in vivo pathology. FIV-PC3'LTR, containing FIV-C36 rev2 and 3' LTR was infectious, although attenuated compared to parental constructs. FIV-PCenv, containing FIV-C36 vif, otfA, env, and the first exon of rev, displayed a phenotype intermediate to parental viruses with regard to replication kinetics, and CD4+ T-cell and neutrophil declines, but peak viral load and development of clinical disease was delayed by three weeks compared to FIV-PPR, FIV-PC3'LTR, and FIV-C36. Studies in Chapter Two evaluate potential mechanisms for the delayed phenotype of FIV-PCenv. To test the hypothesis that delayed kinetics observed during FIV-PCenv infections was due to adaptation of the construct during first round infections, pooled plasma from the in vivo study described in Chapter One was used to inoculate a second cohort of cats. Passaged FIV-PCenv again displayed intermediate phenotype in terms of viral replication and immunopathology, but onset of acute viremia was no longer delayed. To further pinpoint particular genes that contribute to FIV pathogenesis, three additional chimeras were generated using PCR-driven overlap extension as described in Chapter Three. Overlapping-PCR was utilized to produce chimeras with specifically substituted ORF genes encoding the FIV-C36 regulatory proteins Vif and OrfA for those from FIV-PPR; chimeras FIV-PCvif, FIV-PCvif/orfA, and FIV-PCorfA were successfully constructed. Upon infection of the feline MYA-1 T-cell line, all three chimeras produced measurable RT activity. Further, in vitro analysis of FIV-PCvif/orfA demonstrated that this construct had replication properties equal to those of FIV-C36 as measured by viral capsid and RNA genome production.
Keywords: accessory gene; chimera; FIV; lentiviruses; overlapping-PCR; pathology; virology